Ressonâncias do envolvimento e participação com os meios - Machado, Irene (2011)
Inquiring the notion of hot and cold media such as classification, it is proposed here to discuss the processes of involvement and participation, with and in the media, as an exercise in perception and cognition. For this, the article follows on from M. McLuhan explorations on the line of explanation of iconic thought. From the analysis of the coding patterns for light screens it was deduced processes of information transduction and the generation of spaces of simultaneity in time. These are the spaces of resistance and conceptual revision discussed in the essay.